Viability of the treatment of acidic waters of the San Jose mine - Oruro – Bolivia (Research, Society and Development, 2016)
The San José mine is located in the city of Oruro - Bolivia. Acid drainage generated inside the mine, with strongly acidic pH values of 1.2 to 2.5, is pumped to 8 liters per second; without any treatment, it is poured into the environment. Such acidic waters eventually flow into Lake Uru-Uru. The load of dissolved metals in annual tons is: 1 Cd; 11 Cu; Fe 761; 14 Pb; 13 As; 0.3 Sb and Zn 22. The goal of the research was limited to study technical, economic, environmental and socially, alternative treatment of acidic waters of the Mina San Jose from laboratory scale tests and pilot plant. Treatment options studied were: Evaporation - Crystallization; Neutralization - precipitation with lime on the surface; Anoxic limestone drains; and finally, Neutralization - precipitation with lime inside the mine. From the results of the technical, economic, environmental and social assessment it concluded that the last option is the most appropriate. The reactor solid / liquid separation inside mine, an abandoned gallery is 104 m long, 2 m wide and a height of 1.8 m. This allows treatment of 691.2 m3 / day acidic water. Lime consumption as required grout is 6.9 tons per day. The treated water has a pH of 6.7 and meet allowable discharge limits. Finally, the sludge generated are arranged in the abandoned pits that are located 150 m from the discharge point pond therapy.Improper investment cost of the project is US $ 282,686.01 and operational costs amount to US $ 383,918.32 by year.The treatment plant was inaugurated on June 30, 2016.